The influence of independence, corporate governance, and audit quality on the integrity of financial statements - Indah, Sri; Sulistiyowati, Yayuk; Mukoffi, Ahmad; Himawan W, Sukarno (Priviet Social Sciences Journal, 2023)
The aim of this research is to determine the influence of independence, corporate governance and audit quality on the integrity of financial reports in manufacturing companies listed on the IDX partially. The research was conducted based on quantitative methods. Determining the research sample used a purposive sampling method so that a research sample of 6 Food and Beverage Sub-sector manufacturing companies registered on the IDX was obtained. This research data uses manufacturing company financial reports for the 2018-2022 period. The data analysis method used is multiple linear regression. The research results prove that independence has a significant effect on the integrity of financial reports in manufacturing companies with t = 3.542, corporate governance has a significant effect on the integrity of financial reports in manufacturing companies with t = 6.750 and audit quality has a significant effect on the integrity of financial reports in manufacturing companies with t count = 5,733. From the results of this research, it can be understood that independence, corporate governance and audit quality play an important role in improving the integrity of financial reports.